Genetic analysis of Phytophthora sojae populations in Fujian, China. (25th January 2017) - Wu, M.; Li, B.; Liu, P.; Weng, Q.; Zhan, J.; Chen, Q.
Abstract : Phytophthora sojae is a destructive soilborne pathogen causing seedling damping‐off and root rot of soybean ( Glycine max ). The goal of this study was to determine the genetic structure of P. sojae populations in Fujian, China. Nine microsatellite markers were used to investigate the genetic variation in 19 P. sojae populations, sampled from Fujian Province and northeastern China (Jilin and Heilongjiang Provinces) between 2002 and 2013. Overall, a low genetic diversity, Hardy–Weinberg disequilibrium, and an r ¯ d index (an index of association) that was significantly different from zero were detected in populations; these results were consistent with self‐fertilization and clonal modes of reproduction for this pathogen. However, using Bayesian Markov chain Monte Carlo approach, principal component analysis and neighbour joining (NJ) algorithm, the Fujian P. sojae populations clustered into three distinct groups, one of which included most isolates of the northeast populations. What is more, significant estimates of pairwise fixation indices ( F ST ) were detected between most populations, especially in different clusters. It is hypothesized that the cropping system used, the limited dispersal ability, and human‐mediated gene flow may account for the observed genetic structure of P. sojae populations in Fujian, China. In addition, a high virulence frequency of the pathogen on different cultivars carrying known major R genes for resistance, and a rapid increase in virulence frequency, indicated that these major R genes should not be used to manage seedling damping‐off and root rot diseases of soybean ( Glycine max ).